2005
DOI: 10.1093/jee/98.2.415
|View full text |Cite
|
Sign up to set email alerts
|

Stage-specific control of grape berry moth, Endopiza viteana (Clemens) (Lepidoptera: Tortricidae), by selective and broad-spectrum insecticides

Abstract: The insect growth regulators (IGRs) tebufenozide and methoxyfenozide and the broad-spectrum insecticides azinphosmethyl, carbaryl, and fenpropathrin were compared for their activity against adult, egg, and larval stages of the grape berry moth, Endopiza viteana (Clemens) (Lepidoptera: Tortricidae), under laboratory and vineyard conditions. Adult mortality was not affected by exposure to field-equivalent rates of tebufenozide or methoxyfenozide on grape clusters, whereas all the broad-spectrum compounds signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Phoxim (organophosphate) and fenpropathrin (pyrethroid) are high effect, low poison, low leftover and broad-spectrum, and often used for agricultural pest management (Isaacs et al, 2005). Previous studies suggested that phoxim can induce oxidative stress and damages of silkworm larval midgut and silk gland after short-term exposure (Su et al, 2014;Li et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Phoxim (organophosphate) and fenpropathrin (pyrethroid) are high effect, low poison, low leftover and broad-spectrum, and often used for agricultural pest management (Isaacs et al, 2005). Previous studies suggested that phoxim can induce oxidative stress and damages of silkworm larval midgut and silk gland after short-term exposure (Su et al, 2014;Li et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Paralobesia viteana is the target of a majority of the insecticides applied in vineyards in eastern North America. These insecticides are primarily broad‐spectrum toxicants with the more recent addition of reduced‐risk insecticides such as insect growth regulators and naturalytes (Isaacs et al. 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Paralobesia viteana is the target of a majority of the insecticides applied in vineyards in eastern North America. These insecticides are primarily broad-spectrum toxicants with the more recent addition of reduced-risk insecticides such as insect growth regulators and naturalytes (Isaacs et al 2005). Current and anticipated restrictions on availability of broad-spectrum insecticides have increased the need for alternative approaches to pest control, based on new modes of action.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the sole dependence on vineyard growth stage timing may be inadequate for management of P. viteana because phenology varies among cultivars, years, and geographic location (Tobin et al 2001, Timer et al 2010. Further, use patterns of modern insecticides, such as insect growth regulators (IGRs), depend on the seasonality of P. viteana (Isaacs et al 2005, Teixeira et al 2009). Thus, there is a need for reliable tools for scouting and predicting P. viteana infestations in vineyards for pest management purposes.…”
mentioning
confidence: 99%
“…Thus, there is a need for reliable tools for scouting and predicting P. viteana infestations in vineyards for pest management purposes. The use of sex pheromone traps, grape cluster evaluation, and accumulated degree-days can improve the timing of insecticide sprays (Isaacs et al 2005). In addition, reduced-spray programs may lead to reduced impact on natural enemies and greater levels of predation and parasitism of P. viteana (Williamson and Johnson 2005).…”
mentioning
confidence: 99%